A szélsőséges időjárási jelenségek hatásai (Effects of the Extreme Weather Events) - Tamás Molnár; Katalin M. Barna (DETUROPE)
Economist Sir Nicholas Stern warned that the global warming could cause major blow to the world economy than the two world wars and the crisis in the 1930s. But where are we in this process now and what can be expected in the near future and what opportunities we are to curb the negative effects and to slow down the global warming. The world’s population is more than 7 billion people now and we will live more than 9 billion on the planet in 2050 according to the conservative estimation because daily the number of inhabitants increases by approximitaly a quarter of a million people (National Rural Strategy, 2020). The water and ecosystem resources are diminishing due to overuse and the values of ecological footprint are very high especially in the developed countries. The increase of extreme weather events and its effects associated with the global warming have also growing impact on agricultural production. This phenomenon is important because to solve the famine and the water shortage will be much bigger problem due to climate change than today. The VAHAVA reports (change-impact-response) draw also attention to the issue which is also important for experts of climate change: Is it clearly climate change and if so than what the role of the human activity in it is? It seems clear that the assumption is almost poetic as the earth sends clear messages: the concentration of greenhouse gases increased suddenly in the atmosphere (carbon-dioxide, methan, nitrous oxide, etc), the average temperature continues to rise (increasing number of hot records), the sea temperature is also rising, the area of glaciers is shrinking dramatically and prolonged drought and flood waters in some places appear. The habitats of plans and animals, routes of bird migration change. The negative effects of extreme weather events thus represent a broad problem area. The effects can be devide into several groups. Some of them have impact already relatively short-term (for example affect of health of people) another part of them, however, exerts a negative influence in an indirect way for a long period of time. According to our present knowledge these processes are irreversible. The 4th Water Report published by UNESCO is dealing with the one of the biggest problems which draws attention to hazards which are related water quality, groundwater, desertification, land degradation and drought (UNESCO, 2013). The report finds that the water problem occurs globally and it stresses the dangers of „isolated” thinking related to climate chnage. However, the isolated thinking appears not only within the geographical boundaries but it also can be observed in sectors together with the „isolated” solution search. Solution to the problems outlined as an innovation process have already begun in developed countries, however, the developing countries need serious help in that regard. The situation is further aggravated by perpetual competition for water between the ecosystem and socio-economic sectors.